External hydrocephalus and subdural bleeding in infancy associated with transplacental anti-Ro antibodies. Issue 4 (1st April 2011) - Edwards, R J; Allport, T D; Stoodley, N G; O'Callaghan, F; Lock, R J; Carter, M R; Ramanan, A V
Abstract : Background: The isolated finding of an unexplained chronic subdural haematoma in an infant may suggest non-accidental head injury (NAHI). The authors report a previously undescribed cause of multifocal chronic subdural haematoma in infancy which could result in a misdiagnosis of previous NAHI. Methods: Two infants, aged 3 and 4 months of age, presented with progressively increasing head circumference measurements from birth. There was no history of encephalopathy. Retinal haemorrhages were not present. CT and MRI demonstrated bilateral subdural fluid collections over the frontal regions that were consistent with either chronic subdural haematomas or haemorrhagic subdural effusions. In view of the possibility of NAHI, child protection investigations were initiated. Findings: In neither case did the child protection investigations raise concerns. Comprehensive investigations for known haematological and metabolic disorders associated with subdural haematomas or effusions in infants were all normal. In both cases the infant's mother had a history of Sjögren's syndrome and both infants had positive anti-Ro antibody at presentation. Conclusions: Transplacental acquisition of anti-Ro antibodies has been associated with external hydrocephalus. External hydrocephalus has been recognised as a predisposing factor for subdural haemorrhage. These are the first reported cases linking the presence of anti-Ro antibodies and external hydrocephalus with subdural fluid collections in infancy.